Annotated record of the detailed examination of Mn deposits recovered during the COCOTOW expedition in the Southeastern Pacific ocean - Lonsdale, Peter (Supplement to: Lonsdale, P (1976): Abyssal circulation of the southeastern Pacific and some geological implications. Journal of Geophysical Research, 81(6), 1163-1176, https://doi.org/10.1029/JC081i006p01163, 1976)
The abyssal circulation of the Pacific Ocean east of the East Pacific Rise is deduced from hydrographic data, supported by a few direct current measurements. Two main flow paths are recognized: across the Chile Rise into the Chile Basin, and thence northward into the Peru Basin and Panama Basin; and eastward across the East Pacific Rise into the Guatemala Basin and into Bauer Basin. Transform fault troughs are important passages allowing flow across the rises, and the Peru-Chile Trench is the principal channel for inflow to the Peru and Panama basins. The deep water that flows across the East Pacific Rise near the equator has a similar temperature structure to that in the southern Chile Basin, but it is less saline and has lower oxygen concentrations. Along both flow paths the bottom waters become warmer, less saline, and less oxygenated as a result of vertical mixing (intensified near sills), geothermal heating (concentrated at active spreading centers) and in situ decay of organic matter (especially beneath productive surface waters). The regional pattern of abyssal circulation may partly control the distribution of metalliferous pelagic sediments (including both fine-grained precipitates and manganese nodules) and the rates of dissolution of calcareous sediments. Where the deep thermohaline flow is accelerated in narrow passages between basins it has deeply eroded the sea floor and transports sediment as bed load. Steady currents measured in one of these passages exceeded 30 cm/s.